Activity of 3′-hydroxychalcone against Cryptococcus gattii and toxicity, and efficacy in alternative animal models - Palanco, Ana Cerrejón [UNESP]; Lacorte Singulani, Junya De [UNESP]; Costa-Orlandi, Caroline Barcelos [UNESP]; Gullo, Fernanda Patrícia [UNESP]; Strohmayer Lourencetti, Natália Manuela [UNESP]; Gomes, Paulo César [UNESP]; Ayusso, Gabriela Miranda [UNESP]; Dutra, Luiz Antônio [UNESP]; Silva Bolzani, Vanderlan Da [UNESP]; Regasini, Luis Octávio [UNESP]; Soares Mendes-Giannini, Maria José [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (Taylor & Francis, 2017)
Aim: This work aimed to evaluate the activity of 3′-hydroxychalcone against Cryptococcus gattii in planktonic and biofilm forms and their toxicity using alternative animal models. Materials & methods: Minimum inhibitory concentration and minimum fungicide concentration were determined. Biofilm formation and the susceptibility tests were performed by the 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-5-[carbonyl(phenylamino)]-2H-tetrazolium hydroxide assay. Toxicity and efficacy were checked in Danio rerio and Galleria mellonella models. Results: The compound 3′-hydroxychalcone showed fungicidal activity against C. gattii in both planktonic and biofilm forms. The toxicity in zebrafish embryos revealed a low lethal concentration. In G. mellonella, the compound did not show antifungal activity and larvae toxicity. Conclusion: Because of the activity of 3′-hydroxychalcone against C. gattii in vitro, molecular modifications should be made to improve efficacy and to reduce toxicity in vivo. </inline-graphic.
Keywords: antifungal; biofilm; chalcone; cryptococcosis; Galleria mellonella; zebrafish